Review and Evaluation of European National Clinical Practice Guidelines for the Treatment and Management of Active Charcot Neuro-Osteoarthropathy in Diabetes Using the AGREE-II Tool Identifies an Absence of Evidence-Based Recommendations - Renwick, Nichola; Pallin, Jennifer; Bo Jansen, Rasmus; Gooday, Catherine; Tardáguila-Garcia, Aroa; Sanz-Corbalán, Irene; Tentolouris, Anastasios; Jirkovská, Alexandra; Koller, Armin; Korzon-Burakowska, Anna; Petrova, Nina; Game, Frances (Journal of diabetes research, 2024)
Background: Charcot neuro-osteoarthropathy (CNO) is a rare but devastating complication of diabetes associated with high rates of morbidity; yet, many nonfoot specialists are unaware of it, resulting in missed and delayed diagnosis. Clinical practice guidelines (CPGs) have proven useful in improving quality of care and standardizing practice in diabetes and diabetic foot care. However, little is known about the consistency in recommendations for identification and management of active CNO. Aim: The aim of this study is to review European national diabetes CPGs for the diagnosis and management of active CNO and to assess their methodological rigor and transparency. Methods: A systematic search was performed to identify diabetes national CPGs across Europe. Guidelines in any language were reviewed to explore whether they provided a definition for active CNO and recommendations for diagnosis, monitoring, and management. Methodological rigor and transparency were assessed using the Appraisal of Guidelines for Research and Evaluation (AGREE-II) tool, which comprises 23 key items organized within six domains with an overall guideline assessment score of ≥ 60% considered to be of adequate quality to recommend use. Each guideline was assessed by two reviewers, and inter-rater agreement (Kendall's W) was calculated for AGREE-II scores. Results: Seventeen CPGs met the inclusion criteria. Breadth of CNO content varied across guidelines (median (IQR) word count: 327; Q1 = 151; Q3 = 790), and 53% provided a definition for active CNO. Recommendations for diagnosis and monitoring were provided by 82% and 53%, respectively, with offloading being the most common management recommendation (88%). Four guidelines (24%) reached threshold for recommendation for use in clinical practice (≥ 60%) with the scope and purpose domain scoring highest (mean (SD): 67%, ± 23%). The remaining domains had average scores ranging between 19% and 53%. Inter-rater agreement was strong (W = 0.882; p < 0.001). Conclusions: European national CPGs for diabetes provide limited recommendations on active CNO. All guidelines showcased deficits in their methodology, suggesting that more rigorous methods should be employed for diabetes CPG development across Europe.
Keywords: Diabetic Foot; Arthropathy, Neurogenic; lidé; Europe; Evropa; neuropatická artropatie; směrnice pro lékařskou praxi jako téma; diabetická noha; diabetické neuropatie; Diabetic Neuropathies; Practice Guidelines as Topic; Evidence-Based Medicine; medicína založená na důkazech; Humans